Comparison of Two Exercise Methods on Motor Performance and Balance in Children with Spastic Cerebral Palsy - Ahmad Ebrahimi-A'tri; Ali Akbar Hashemi-Javaheri; Leila Asghari (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: The purpose of this study was to assess the effects of two exercise methods on improving balance and motor performance in children with spastic diplegia cerebral palsy. Design: Randomized clinical trial. Materials & Methods: In this semi-experimental study 21 children aged 7-12 years, with spastic diplegia cerebral palsy, who were independent ambulators, were recruited. Children were randomly assigned into a control group (n=7), home exercise group (n=7) and clinic exercise group (n=7). The control group received regular daily activities, the home exercise group performed regular daily activities plus a sit-to-stand and step-up exercise programmes for six weeks at home and the clinic exercise group was given the same exercise programmes in clinic. Gross motor ability was tested by gross motor function measure (GMFM) test. Timed Up and Go Test and Functional Reach Test were used to measure functional balance. Walking performance was assessed using the 10-m walking test. Results: At the end of the intervention period, a statistically significant increase in the mean Functional Reach Test in two exercise groups and a reduction in the mean of Timed Up and Go Test were noted (P<0.05). No statistically significant changes were recorded in the control group. In all other assessed no outcomes significant differences were noted between the groups. Conclusion: A sit-to-stand and step-up exercise programmes can improve balance performance in children with spastic diplegia cerebral palsy in clinic and home.